2013
DOI: 10.3357/asem.3669.2013
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Cues for Orienting Pilots During Hover Over Moving Targets

Abstract: The results support the efficacy of the tactile system in providing directional cues for maintaining pilot performance during a hover maneuver over a moving target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…It has long been known that situations where the locally-defined “up and down” are ambiguous or unexpected can elicit disorientation and motion sickness symptoms among astronauts (Nicogossian et al, 1988). It is also known that providing a tactile reference can aid with orientation and performance during spaceflight (Lackner and DiZio, 2000; van Erp and van Veen, 2006; Clément et al, 2007) or piloting of an aircraft (Rupert, 2000; Kelley et al, 2013; Brill et al, 2014). In these cases, body tilt or motion that has not been perceived correctly causes the tactile cue to vibrate much like a rumble strip vibrates a driver who is veering off the road.…”
Section: Plausible Strategies For Studying and Facilitating Sensorimomentioning
confidence: 99%
“…It has long been known that situations where the locally-defined “up and down” are ambiguous or unexpected can elicit disorientation and motion sickness symptoms among astronauts (Nicogossian et al, 1988). It is also known that providing a tactile reference can aid with orientation and performance during spaceflight (Lackner and DiZio, 2000; van Erp and van Veen, 2006; Clément et al, 2007) or piloting of an aircraft (Rupert, 2000; Kelley et al, 2013; Brill et al, 2014). In these cases, body tilt or motion that has not been perceived correctly causes the tactile cue to vibrate much like a rumble strip vibrates a driver who is veering off the road.…”
Section: Plausible Strategies For Studying and Facilitating Sensorimomentioning
confidence: 99%
“…Vibrotactile displays are proving to be a useful adjunct to visual and auditory displays, as demonstrated in various complex and "event-driven" professional domains such as aviation, navigation, interface design, and healthcare (Hameed, Ferris, Jayaraman, & Sarter, 2009;Jones, Lockyer, & Piateski, 2006;Kelley et al, 2013). Evidence suggests that vibrotactile devices are reliable (Jones et al, 2006), and can be as effective as visual or auditory displays (Ferris & Sarter, 2011;Ngo & Spence, 2010) at alerting clinicians to changes in patient status.…”
Section: Vibrotactile Technology In Healthcarementioning
confidence: 99%
“…In a helicopter study pilots were able to stay closer to a moving target during hover when using a tactile display (than without) and they also rated their situation awareness as higher when they used the tactile display [8]. Curry and Estrada [5] showed that a tactile belt significantly improved drift control during takeoff and hover in helicopters.…”
Section: Introductionmentioning
confidence: 99%